Keesha's house - Frost, Helen, 1949- (New York : Square Fish, 2013)
Seven teens facing such problems as pregnancy, closeted homosexuality, and abuse each describe in poetic forms what caused them to leave home and where they found home again.
School Library Journal starred
Wilson's Junior High School
Wilson's Senior High School
Book Links (A.L.A.), April 2003
Booklist, March 2003
Five Owls, April 2004
Keywords: Dysfunctional families -- Juvenile fiction; Home -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Teenagers -- Juvenile fiction; Family problems -- Fiction; Home -- Fiction; Interpersonal relations -- Fiction; Novels in verse; Teenagers -- Fiction; Family problems -- Fiction; Home -- Fiction; Interpersonal relations -- Fiction; Novels in verse; Teenagers -- Fiction